2008
DOI: 10.1196/annals.1414.036
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Bacteria as Effectors in Cancer Immunotherapy

Abstract: Despite the great strides made in understanding the basic biology of cancer and the multiple approaches to cancer therapy that have been utilized, cancer remains a major cause of death worldwide. The two properties that define the most successful tumors are low antigenicity, enabling cancer cells to escape immune system recognition, and high tumorigenicity, allowing the cells to proliferate aggressively and metastasize to other tissues. The development of novel anticancer therapies is aimed at enhancing the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…In this study, increased neutrophil infiltration was observed only in tumors infected with the Fas-expressing Salmonella strain [178]. Finally, Salmonella has been also used as a vector for delivering proinflammatory cytokines, such as IL-2, to increase tumor immunogenicity and prevent tumor growth in a mouse melanoma model [179].…”
Section: Delivery Of Exogenous Dna By Atten-uated Salmonellamentioning
confidence: 61%
“…In this study, increased neutrophil infiltration was observed only in tumors infected with the Fas-expressing Salmonella strain [178]. Finally, Salmonella has been also used as a vector for delivering proinflammatory cytokines, such as IL-2, to increase tumor immunogenicity and prevent tumor growth in a mouse melanoma model [179].…”
Section: Delivery Of Exogenous Dna By Atten-uated Salmonellamentioning
confidence: 61%
“…The procedure for implanting B16.F1 tumor cells in syngeneic C57Bl/6 mice has been described [21], [22]. Briefly, 8-week-old mice were implanted s.c. with 2×10 5 B16.F1 cells and staged to day 11.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Avogadri et al and Al Ramadi et al revealed that attenuated S . typhimurium infects malignant cells and triggers an anti-cancer immune response (26,27). Furthermore, S .…”
Section: Discussionmentioning
confidence: 99%